AL-MANIHAH AS AN ALTERNATIVE CONCEPT IN THE DEVELOPMENT OF SME IN INDONESIA - Ahmad Dahlan Malik (Universitas Airlangga, 2015)
The development of the small and medium enterprises (SMEs) is encouraged in Indonesia because the SMEs were proven to be more sustainable than corporations during the economic crisis in 1997. Such the SMEs are In Islam, it is represented by entrepreneurship that has long been encouraged along with the Shari’ah. During the era of caliph Umar Ibn Abdul Aziz, the poverty was eliminated due to the role of Islamic economic welfare system. In development of the economic welfare system, the concept of Al-Manihah will play one of the important roles. Al-Manihah encourages the establishment of Islamic civilization and development of the SMEs based on maqasid shari’ah in the era of Sahabah(companions) and Islamic Financial Institution for current era. In addition, Al-Manihah is one of the alternatives to overcome the risk in financing SME towards Islamic financial institutions. The concept of Al-Manihah for development of SME through SWOT analysis and mix method research design show positive correlation between Al-Manihah concept and development of SMEs. Keyword : Small and Medium Enterprise (SME), Al-Manihah, Islamic Financial Institution, SWOT analysis, and Mix Method Research Design